Bletchley Park and the Development of the Rockex Cipher Systems: Building a Technocratic Culture, 1941–1945. (April 2017) - Smith, Christopher
In 1943 Britain's security experts began to investigate the development of new cipher machine technologies. This resulted in the creation of the initial projects to construct the Rockex family of cipher systems. The development of the systems marked a major step in the building of a technocratic culture within Britain's primary wartime cryptanalysis agency, the Government Code and Cypher School housed at Bletchley Park. This article explores the evolution of Bletchley Park's wartime technocratic culture and utilizes the Rockex project as a case study; moreover it establishes the importance of the project as a catalyst of further institutional cultural change.